Silastic Splints in Nasal Surgery - Muhammad Waal , Naar Alam Ansari, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To determine the outcome of nasal septa! surgery with & without Silastic splints in term of adhesion formation, pain, discomfort and crusting experienced by the patient. Study: Comparative, interventional study. Place & Duration: Department of ENT, PUMHS Hospital Nawabshah, from October 2009 to April 2010 Material and Methods Total 50 patients under going septal surgery. We divided patients in two groups. Group A & B. Group A intra nasal splints with finger packing and group B without intra nasal splints with finger packing. Follow-up was carried out at 48 hours and 01 week for assessment of crust and pain, while adhesion formation was monitored for 01 and 02 months after surgery. Results: Age of patient in group A and B was 20 to 45 years. There was a marked difference in findings i.e. crusts and adhesion with B Group (Without intra nasal splint) and Group A with intra nasal splint have only pain and discomfort. Conclusion : Insertion of silastic splints after septal surgery should be accepted as a routine procedure.